2005
DOI: 10.1007/s00270-004-8236-3
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Following Uterine Artery Embolization with Polyvinyl Alcohol Particles for Patients with Uterine Fibroid or Adenomyosis

Abstract: Although the absolute number of cases was small, UFE with PVA particles ultimately did not affect fertility in the women who underwent the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…To date, only a few clinical studies, all using PVA as embolic agent, report successful deliveries after UAE (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Only Pron et al and the Ontario Uterine Fibroid Embolization collaborative group (9) have reported that of 35 women trying to conceive after embolization with 355-500 mm PVA, 21 women, of average age 34 years (range, 27-42 y), became pregnant.…”
Section: Fertilitymentioning
confidence: 93%
See 2 more Smart Citations
“…To date, only a few clinical studies, all using PVA as embolic agent, report successful deliveries after UAE (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Only Pron et al and the Ontario Uterine Fibroid Embolization collaborative group (9) have reported that of 35 women trying to conceive after embolization with 355-500 mm PVA, 21 women, of average age 34 years (range, 27-42 y), became pregnant.…”
Section: Fertilitymentioning
confidence: 93%
“…Cases of intrauterine growth retardation have indeed been reported after hypogastric artery ligation (19,74) or UAE (18,20). In his retrospective analysis of 50 published cases of pregnancy after UAE, Goldberg et al (7) found that women who become pregnant after UAE are at risk for conceiving newborns with smallness for gestational age (7%).…”
Section: Hypotrophymentioning
confidence: 96%
See 1 more Smart Citation
“…To date, there have not been significant data about pregnancy outcomes after surgical occlusion or embolization of the uterine artery. A systematic search of the biomedicine database MEDLINE from 2000 to 2005, using terms such as fibroid, pregnancy, and uterine artery, identified only a limited number of clinical studies (2)(3)(4)(5)(6)(7)(8)(9)(10), with the exception of case reports. Only one pilot study of the available literature contains data prospectively comparing pregnancy results between uterine artery embolization (UAE) and laparoscopic uterine artery occlusion (LUAO) (11).…”
mentioning
confidence: 99%
“…Few articles have focused on the effect of UAE for fibroids and its outcome on future fertility and pregnancy. To the best of our knowledge, pregnancy after UAE has been described in the literature in the form of case reports [17][18][19][20], a review article [21], and retrospective reports of case series [22][23][24][25][26][27][28][29]. As of March 2008, more than 170 patients worldwide had become pregnant after UAE.…”
mentioning
confidence: 99%